2016
DOI: 10.14260/jemds/2016/1464
|View full text |Cite
|
Sign up to set email alerts
|

A Comparative Study of Typhidot Test and Widal Test With the Culture-Positive Typhoid Fever in Children

Abstract: BACKGROUNDTyphoid fever in children is a common childhood infection in both urban and rural regions in tropical countries. Clinical presentation is varied and overlaps many other acute febrile illness. MATERIALS AND METHODSStudy was a prospective descriptive study. The study was conducted in Institute of Child Health and Hospital for Children, Egmore, Chennai, Tamilnadu during the period of April 2013 to November 2015. Children aged 3-12 years with fever more than 5 days with no obvious focus of infection. Coa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
6
0

Year Published

2020
2020
2021
2021

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(6 citation statements)
references
References 9 publications
0
6
0
Order By: Relevance
“…Typhidot IgM positive means early phase of illness while both IgM and IgG are positive in case of middle phase of infection. IgG antibodies are not indicative of acute infection as they persist in serum of the patient for about 2 years of infection [12].…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Typhidot IgM positive means early phase of illness while both IgM and IgG are positive in case of middle phase of infection. IgG antibodies are not indicative of acute infection as they persist in serum of the patient for about 2 years of infection [12].…”
Section: Discussionmentioning
confidence: 99%
“…The usefulness of Typhidot is quite profound in the diagnosis of typhoid fever. It is easy to perform, and results are interpreted quickly [12]. There is no need of an ELISA reader to evaluate the results.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The Widal test parameters obtained in the present study show some general patterns with some previous studies that are high sensitivity, low predictive value of the positive test, and high predictive value of the negative test. For example, in the study conducted by Muthaiyan [ 24 ] and collaborators, they reported a sensitivity of 88.5% (95% CI: (69.82–97.42)), a specificity of 81.56% (95% CI: (74.16–87.58)), a positive predictive value of 46.94% (95% CI: (32.54–61.720)), and a negative predictive value of 97.46% (95% CI: 92.74–99.44) for the Widal slide agglutination test. In a similar study in India in 2016 [ 24 ], the authors reported a sensitivity of 80.77% (95% CI: (60.64–97.42)), a specificity of 78.01% (95% CI: (70.22–84.54)), a positive predictive value of 40.38% (95% CI: (27.01–54.90)), and a negative predictive value of 95.65% (95% CI: ()90.14–98.56)).…”
Section: Discussionmentioning
confidence: 99%
“…For example, in the study conducted by Muthaiyan [ 24 ] and collaborators, they reported a sensitivity of 88.5% (95% CI: (69.82–97.42)), a specificity of 81.56% (95% CI: (74.16–87.58)), a positive predictive value of 46.94% (95% CI: (32.54–61.720)), and a negative predictive value of 97.46% (95% CI: 92.74–99.44) for the Widal slide agglutination test. In a similar study in India in 2016 [ 24 ], the authors reported a sensitivity of 80.77% (95% CI: (60.64–97.42)), a specificity of 78.01% (95% CI: (70.22–84.54)), a positive predictive value of 40.38% (95% CI: (27.01–54.90)), and a negative predictive value of 95.65% (95% CI: ()90.14–98.56)). Sherwal et al [ 25 ] also reported a sensitivity of 74%, a specificity of 83%, and a positive predictive value of 87.5%.…”
Section: Discussionmentioning
confidence: 99%